The significance of Psalm 121 in an African context - Adamo, David T. (Journal for Semitics, 2017)
The interpretation of Psalms has gone through diverse and seemingly strange stages over time. This article deals with a review of the interpretation of Psalms from the beginning to the present in Africa. After a brief review of the history of Psalm study, it critically examines the history and significance of Psalm 121 in an African context. The Euro-American interpretation follows different types of criticism, such as source, form, and rhetorical criticism, amongst others. However, Africentric scholars mainly follow what we may call an “African biblical hermeneutics” type of interpretation. In this case, Psalm 121 in an African context is regarded as a psalm of protection, healing, and success to meet the existential need of African people. The repetitive reading, the chanting, and the writing of this Psalm on door-posts, motor vehicles, parchments, and clothes is seen as taking up the identity of ancient Israel, the first readers, with the expectation that God will repeat the same ancient miracles, of protection, healing, success. Reading and chanting or writing Psalm 121 Africentrically means a re-enactment of events in the life of ancient Israel for the purpose of transformation in readers’ lives. It is considered a reaffirmation of singers’ and chanters’ faith in the God of Israel to protect, heal, and bring success.
free